1995
DOI: 10.1902/jop.1995.66.9.808
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Genetic Agranulocytosis (Kostmann Type). A Case Report

Abstract: Severe periodontitis in a patient with infantile genetic agranulocytosis (Kostmann syndrome) is presented. This rare syndrome is inherited as an autosomal recessive pattern and characterized by severe neutropenia. The periodontal status and treatment of the patient is described. It is concluded that periodontal therapy including scaling, root planning, soft tissue curettage, and the use of selected antimicrobial agents can be successful in this particular syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…A case report implicates herpes viruses in the pathogenesis of the periodontal defects associated with the condition (112). It has been suggested that a therapeutic regimen consisting of scaling and root planing, soft‐tissue curettage and the use of selected antimicrobial agents could be successful in the resolution of periodontal infection in subjects inflicted with this syndrome (77).…”
Section: Diseases Associated With Neutrophil Disordersmentioning
confidence: 99%
“…A case report implicates herpes viruses in the pathogenesis of the periodontal defects associated with the condition (112). It has been suggested that a therapeutic regimen consisting of scaling and root planing, soft‐tissue curettage and the use of selected antimicrobial agents could be successful in the resolution of periodontal infection in subjects inflicted with this syndrome (77).…”
Section: Diseases Associated With Neutrophil Disordersmentioning
confidence: 99%
“…A further neutrophil deficiency is found in infantile genetic agranulocytosis, a rare autosomal recessive disease where polymorphonuclear leukocyte numbers are very low and which has been associated with aggressive periodontitis (144).…”
Section: Evidence For the Role Of Genetic Variants In Periodontitismentioning
confidence: 99%
“…The association of severe periodontitis with a decrease in the number of circulating neutrophils is well documented in the literature. Situations such as neutropenia, agranulocytosis (Hou & Tsai 1988, Lamster et al 1987, Saglam et al 1995, Zubery et al 1991, Watanabe 1990, cyclic neutropenia (Rylander & Ericsson 1981, Scully et al 1982, Prichard et al 1984, Baer & Iacono 1994, Pernu et al 1996, da Fonseca & Fontes 2000, chronic benign neutropenia (Reichart & Dornow 1978), chronic idiopathic neutropenia (Baehni et al 1983, Kamma et al 1998, and familial benign chronic neutropenia (Deasy et al 1980, Stabholz et al 1990, Kirstila et al 1993, Porter et al 1994, are all asso-ciated with periodontitis. In neutropenic patients, the number of neutrophils sometimes can be restored with external administration of haematopoietic colony-stimulating factors, such as granulocyte colony-stimulating factor.…”
Section: Neutrophil Disorders Predispose To Periodontitismentioning
confidence: 99%